A multidisciplinary approach to the preterm birth - M. D. Andreeva; R. A. Agajan; A. N. Akhidzhak (Акушерство, гинекология и репродукция)
Introduction. Rate of factors affecting preterm birth development has not been fully elucidated. The assessment was carried out by identifying 1-2 causes used to build up prognosis.Aim: to identify most relevant risk factors for preterm birth and assess their impact on pregnancy.Materials and Methods. The prospective comparative study was conducted that included group 1 - 36 women with term pregnancy, group 2 - 35 with preterm labor. Establishment of the menstrual cycle has been studied by assessing reproductive, somatic history, and course of current pregnancy.Results. The postpartum women from group 2 were characterized by older age (30.42 ± 6.19 years; p = 0.038). The groups differed by the age of menarche: in group 2, its onset was recorded earlier (11.31 ± 0.79 years), showing shorter duration of menstruation (4.25 ± 1.26 days) as well as menstrual cycle (27.71 ± 3.46 days). Infections in puberty were substantially more frequent in postpartum women from group 2: group 2 vs. group 1 - in 21 vs. 8 postpartum women (p < 0.001); a history of urinary tract infections was also more common in group 2 (in 17 puerperas; p = 0.003), that is also typical for cases resulting in preterm pregnancy. The causative agent of bacterial vaginosis in group 2 was more often presented by Atopobium vaginae (in 17 puerperas; p = 0.0001), with Gardnerella vaginalis found less frequently (in 13 puerperas; p = 0.024), which is important to know for selecting proper therapy. During full-term pregnancy, the Lactobacillus crispatus strain, that determines vaginal health, was excreted significantly more often (in 29 puerperas; p = 0.009). Anemia affecting the antenatal fetal development and the course of labor was significantly more frequent in group 2 (in 22 puerperas; p < 0.001).Conclusion. While planning pregnancy, it is necessary to take into account the age, menstrual cycle features, history of former infections, vaginal microbiota features, as well as conduct proper therapy and prevention in pregravid period.